The role of D-serine and glycine as co-agonists of NMDA receptors in motor neuron degeneration and amyotrophic lateral sclerosis (ALS) - Paul, Praveen; de Belleroche, Jackie (Frontiers in Synaptic Neuroscience, 2014)
The fundamental role of D-serine as a co-agonist at the N-methyl-D-aspartate receptor (NMDAR), mediating both physiological actions of glutamate in long term potentiation and nociception and also pathological effects mediated by excitotoxicty, are well established. More recently, a direct link to a chronic neurodegenerative disease, amyotrophic lateral sclerosis/ motor neuron disease (ALS) has been suggested by findings that D-serine levels are elevated in sporadic ALS and the G93A SOD1 model of ALS (Sasabe et al., 2007; 2012) and that a pathogenic mutation (R199W) in the enzyme that degrades D-serine, D-amino acid oxidase (DAO), co-segregates with disease in familial ALS (Mitchell et al., 2010). Moreover, D-serine, its biosynthetic enzyme, serine racemase (SR) and DAO are abundant in human spinal cord and severely depleted in ALS. Using cell culture models, we have defined the effects of R199W- DAO, and shown that it activates autophagy, leads to the formation of ubiquitinated aggregates and promotes apoptosis, all of which processes are attenuated by a D-serine/glycine site NMDAR antagonist. These studies provide considerable insight into the crosstalk between neurons and glia and also into potential therapeutic approaches for ALS.